Biological diversity of cultural plants - a basis of innovative development of crop production - I. V. Savchenko (Аграрная наука Евро-Северо-Востока, 2017)
The analysis of a condition and use of genetic resources is done. The general gene pool of the crops kept at institutes of Russia constitutes 370 thousand samples. On the basis of a gene pool 260-350 grades and hybrids of agricultural and medicinal cultures with high rates of product quality, steady against abiotic and biotic stresses were created in the country with modern genetic and selection methods, including biotechnological with use of molecular and genetic marking. All this work is carried out in 42 breeding centers of Russia. Successful breeding activity is done in centers for grain crops in the Krasnodar’s SRIA, All-Russian Research Institute of grain crops, SRIA S.E., WSRIA, the Volga region SRIA, SRIA of Northern Trans-Urals; for garden crops on All-Russian SITGN Joint, project company of the All-Russian Research Institute, SKZNIISIV; for fodder crops (SRIA All-Russian Research Institute of forages, the All-Russian Research Institute of rape). In the Krasnodar SRIA more than 100 grades of highly effective grades of winter wheat are created. For creation of a grade it is spent 6.8-8.9 million rubles here, and economic effect of cultivation of a grade makes more than 4 billion rubles. In the Moscow breeding center the academician Sandukhadze B.I. creates varieties of winter wheat with productivity of 8-11 tons/hectare for a black earth zone of Russia where earlier fodder grain was grown up. In Russia 77 varieties of winter rye are cultivated. Scientists of the Moscow SRIA, ZNIISH NE, Bashkir SRIA, SRIA SE, as all-Russian Institute of plant and others successfully work with a gene pool of rye. In SRIA NE, SibNII of forages and the Ural NIISH the highly productive varieties of oats resistant against drowning, fall and diseases are received. Scientists of gardening and vegetable growing with use of modern methods of selection created varieties, highly productive with high qualitative indexes, and hybrids. 128 species (8 thousand hybrids) of vegetable - melon cultures are brought in the State Registry of agricultural achievements. For a humid zone of Russia 139 varieties of a clover with high quality and productivity are created. In All-Russian research Institute of medicinal and aromatic plants the gene pool of herbs is kept and studied (1272 species in the Botanical garden and 273 species of tropical flora in greenhouses)